(untitled) (Revista Científica Ciencias Naturales y Ambientales, 2025)
This research was carried out on six of the 21 farms in the Rio Mariano community, covering a total of 126 hectares, equivalent to 36% of the community’s surface area. The objective was to evaluate the level of sustainability in order to design appropriate agroecological strategies for these productive units. An initial diagnosis was carried out to characterise the study area. Subsequently, environmental, social and economic sustainability indicators were analysed using weighting criteria, which made it possible to determine the overall level of sustainability of the production units. The results revealed that the predominant economic activity is agriculture, followed by livestock, with cocoa (Theobroma cacao L.) being the most frequent crop, present in 83.33% of the farms. From the evaluation of the economic, social and environmental indices, it was determined that three of the six farms exceeded the minimum threshold of the General Sustainability Index (ISGen > 2). However, only one farm achieved values above the threshold in all three dimensions, which allows it to be considered truly sustainable. Consequently, the AMEBA diagram showed that all the farms had weaknesses in the management of temporal and spatial biodiversity, as well as other deficiencies in the different dimensions evaluated. Based on these findings, agroecological strategies were proposed to strengthen the indicators with the lowest level of sustainability, aimed at strengthening the most vulnerable components and promoting sustainable and integrated farm management.